Moderate Islamic Values in the Life of the Prophet Muhammad SAW in the Book Ar-Rahiq al-Makhtum by Sofyyu AL-Rohman Mubaroqfury - Hartono, Muslih; Yenuri, Ali Ahmad (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
Şofyyu Al-rohman Mubaroqfüry bin Abdullah bin Muhammad Ali bin Abdul Mu'min bin Faqirullah Al-Mubāroqfüry, or more often referred to as Şofyyu Al-rohman Mubaroqfüry. He was born on January 6, 1943 AD, he is a scholar who is an expert in the field of siroh with his famous book, namely al-rohyq al-makhtum. This type of research is library research because it collects data using documentation sourced from library writings. The results of this research are 1) There are moderate values ​​in the life of the Prophet SAW in the Book of Ar-Rahiq Al-Makhturm by Syaikh Syafiyyur Rahman Al-Mubarakfuri which can be gleaned from six moments, namely the Sirah Nabawiyah moments before prophethood, the Mecca preaching, the migration to Ethiopia, the Medina charter, the hudaibiyah agreement, and the Medina declaration; and 2) The moderate Islamic values ​​contained in the life of the Prophet Muhammad provide very relevant and important guidance for Muslims in facing current social challenges and changes